Queer Educators in Schools: The Experiences of Four Beginning Teachers - Tompkins, Joanne; Kearns, Laura-Lee; Mitton Kükner, Jennifer (Canadian Journal of Education/Revue canadienne de l’éducation, 2019)
What are the experiences of beginning queer educators? We followed four LGBTQ-identified teachers as they began their teaching careers. As pre-service teachers, they took on leadership roles advocating for LGBTQ-inclusive education. Their stories were diverse: from feeling empowered and accepted, to being conflicted about coming out, to being the sole advocate for LGBTQ-inclusive education, to experiencing school leadership and climates that ranged from supportive to hostile. We are encouraged by their resilience and agency, yet deeply concerned by some of their negative experiences. Systemic work remains to be done not only for LGBTQ youth but also for LGBTQ educators in schools.